Two dimensional array based overlay network for balancing load of peer-to-peer live video streaming - Ibrahimy, Abdullah Faruq Ibn; Islam, Md. Rafiqul; Anwar, Farhat; Ibrahimy, Muhammad Ibn (2013)
The live video data is streaming usually in a tre e-based overlay network or in a mesh-based overlay network. In case of departure of a peer with additional upload bandwidth, the overlay network becomes very vulnerable to chur n. In this paper, a two dimensional array- based overlay network is proposed for streaming the live video stream data. As there is always a peer or a live video streaming server to upload t he live video stream data, so the overlay network is very stable and very robust to churn. Pe ers are placed according to their upload and download bandwidth, which enhances the balance of l oad and performance. The overlay network utilizes the additional upload bandwidth of peers to minimize chunk delivery delay and to maximize balance of load. The procedure, whi ch is used for distributing the additional upload bandwidth of the peers, distributes the addi tional upload bandwidth to the heterogeneous strength peers in a fair treat distri bution approach and to the homogeneous strength peers in a uniform distribution approach. The proposed overlay network has been simulated by Qualnet from Scalable Network Technolo gies and results are presented in this paper.